Strand level modeling of contact resistance and coupling loss for EU-DEMO-TF prototype conductors. (12th September 2019) - Bagni, T; Devred, A; Nijhuis, A
Abstract: The development of the toroidal field coils of the upcoming European DEMO reactor is under the coordination of the EUROfusion Consortium. The Swiss Plasma Center (SPC) and ENEA-Fusion proposed two new cable concepts, WP1-RW1 (react and wind) and WP2-WR1 (wind and react), both with rectangular cross section and inspired by existing concepts of Nb3 Sn cable-in-conduit conductors. The prototypes were experimentally tested on AC loss and inter-strand contact resistance at the University of Twente. The code JackPot-AC/DC, developed at the University of Twente, is used to model the conductors' geometry and to study their electromagnetic behavior. The experimental results are used to calibrate and benchmark the simulations. The analysis of coupling loss and current distribution shows the impact of the magnetic field orientation on the rectangular shape of the sample's cross section, focused on possible issues for the stability and performance of the conductors. One notable outcome of the study is the level of maximum allowable coupling loss in the conductors, depending on the magnetic field orientation, based on the peak electric field threshold defined for the ITER CS conductors in previous JackPot studies.